The situation of working environment will affect the job performance of employees at Perbadanan Kemajuan Negeri Melaka / Suraiti Shahedi - Shahedi, Suraiti (Faculty of Business and Management, 2007)
Positive working environment has been identified as a driver of performance. It is important because employee valuations of the environment will influence their job performance. Nowadays, numbers of civil servants that suffer from workplace situation have increase. So that it is important for management to manage their working environment and improve weaken area. This study is a research of 'The Situation of Working Environment Will Affect the Job Perfomance of Employees at Perbadanan Kemajuan Negeri Melaka'. The study utilize questionnaire as the instrument for collecting data. Questionnaires have been distributed to 40 employees from all departments at the organization to do the research.